2015
DOI: 10.1186/s13104-015-1251-4
|View full text |Cite
|
Sign up to set email alerts
|

Healing activity of Casearia sylvestris Sw. in second-degree scald burns in rodents

Abstract: BackgroundEvery year thousands of people are victims of burns, mainly scald burns. Many of these victims have small size wounds and superficial partial thickness and do not seek specialized medical care. As in Brazil Casearia sylvestris Sw., popularly known as guaçatonga is widely used for its analgesic, antiseptic and anti-inflammatory activities, this study sought to evaluate the effects of its hydroalcoholic extract in healing process of burns injuries.MethodsThe obtained extract was validated applying a th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 37 publications
2
14
0
5
Order By: Relevance
“…Deep second-degree scald burns involve the deep dermis and a small amount of residual deep skin attachments (25). The fibroblasts proliferate to fill the wound and the epidermal stem cells proliferate and differentiate to form new epidermis and complete repair (26). In the present study, H&E and Masson staining demonstrated that miR-27b inhibition on day 21 post-modelling significantly increased the number of fibroblasts and collagen in the wound surface and reduced the infiltration of inflammatory cell.…”
Section: Discussionsupporting
confidence: 61%
“…Deep second-degree scald burns involve the deep dermis and a small amount of residual deep skin attachments (25). The fibroblasts proliferate to fill the wound and the epidermal stem cells proliferate and differentiate to form new epidermis and complete repair (26). In the present study, H&E and Masson staining demonstrated that miR-27b inhibition on day 21 post-modelling significantly increased the number of fibroblasts and collagen in the wound surface and reduced the infiltration of inflammatory cell.…”
Section: Discussionsupporting
confidence: 61%
“…The extract from leaves of C. sylvestris also presents angiogenic effects in the repair of skin burns [47] and in this study, blood vessels increase and a gradual decrease of VEGF was observed in the groups treated with this extract, showing its efficacy in the modulation of this pro-angiogenic factor. Ferrara [54] reports that VEGF has a fundamental action for adequate tissue repair and it promotes the growth of endothelial cells derived from arteries and veins, contributing to the formation of new vessels with increased vascular permeability.…”
Section: Sylvestris and Angiogenesissupporting
confidence: 67%
“…Second-degree scald burns treated with hydroalcoholic extract of C. sylvestris in non-diabetic rats showed good healing results attributed to the inhibition of the synthesis of inflammatory mediators stimulated by active extracts (clerodanic diterpenes), suggesting its therapeutic potential in the treatment of the inflammatory conditions of these injuries [47]. Therefore, the results obtained in our study also indicated that C. sylvestris favorably modulates the inflammation in diabetics animals, highlighting its importance in the repair of 2nd-degree burns in diabetes.…”
Section: Sylvestris and The Inflammatory Processmentioning
confidence: 99%
“…45 Casearia sylvestris, a native tree from Mexico, Central, and South America, and popularly known as Guaçatonga, with great ecological, pharmacological and commercial importance, also has important healing properties. 46 Campos et al 47 treated second-degree burns on the back of rats with hydroalcoholic extracts of leaves of C. sylvestris which accelerated the repair of burns inhibiting the synthesis of inflammatory mediators. This result suggests the therapeutic potential of this species in the treatment of inflammatory conditions as it occurs in this type of injury.…”
Section: Tissue Healing and Phytotherapeuticsmentioning
confidence: 99%